Extended reality in skull base surgery: a systematic literature review - Sanker, Vivek; Nordin, Emil O. R.; Badary, Amr; Eberle, Adam T.; Ramanan, Sudarshan; Jensen, Kate N.; Miller, Margaux E.; Catapano, Joshua S.; Huguenard, Anna L.; Rahmani, Redi; Lawton, Michael T. (Frontiers in Surgery, 2025)
IntroductionExtended reality (XR) technology may play an important role in progressing the field of skull base surgery. Its potential use in neurosurgical training, case preparation, and the operating room could make XR a powerful addition to the surgical toolbox. This study evaluated the application of XR in skull base surgery.MethodsA systematic literature search from inception to March 28, 2024, was performed using 4 databases: PubMed, Scopus, Web of Science Advance, and Embase (Ovid). Original studies involving the use of XR in skull base surgery for surgical planning or training purposes were included. Conference abstracts, reviews, and case reports were excluded.ResultsOf 357 articles screened across all 4 databases, 250 were included. After careful evaluation of titles and abstracts for eligibility, 29 articles were deemed suitable for full-text examination. A subsequent detailed assessment excluded 8 articles, resulting in a final 21 studies that met the criteria for inclusion in the systematic review. Of the 21 studies included, 13 (62%) focused on augmented reality, 4 (19%) focused on virtual reality, and 4 (19%) focused on mixed reality. Augmented reality has demonstrated varying degrees of effectiveness, with mean registration accuracy reported between 2.5 and 10.75 mm. The mean (SD) registration error reported in mixed reality was 5.76 (0.54) mm. Virtual reality has been used for preoperative planning and intraoperative guidance, with average computation times ranging from 15 s to 2 min.DiscussionThe role of XR in skull base surgery is anticipated to grow, given its potential for streamlining surgical planning, neuronavigation, and teaching. Although the use of XR in skull base surgery shows promise, the technologies associated with these modalities require substantial improvement before XR is a stable component of the neurosurgical toolbox.